2005
DOI: 10.1258/rsmmsl.45.3.205
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Burns for Wound Ageing reveals Changes in Unburnt Skin with Implications for Future Research

Abstract: Thirty-three punch biopsy sets of burn wound edge and adjacent unburnt skin from burn wounds aged six hours to 23 days were obtained from 18 patients. Immunohistochemical staining was performed for transforming growth factor beta receptor, epidermal growth factor receptor and MIB-1 (which stains the cell cycle associated antigen ki-67) in addition to integrins alpha V, 5 and 3 to assess for temporal patterns that might assist in the ageing of burn wounds. There was an early (12hr-4day) rise in integrin alpha V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…This finding can be considered relevant when referring to data previously outlined in a study aiming to describe the basic immunohistology of burn wound and adjacent unburned skin: An initial peak of Ki67 labeling was reported in both areas just after burn injury, followed by a marked labeling decrease after 20 days post-injury (number of positive cells being ≤5). [12] In the present study with continuous GHB infusion, the evolution pattern was the opposite: The number of positive cells remained quite much high. This could be explained by the mitogen effect of IGF1 on keratinocytes.…”
Section: Discussioncontrasting
confidence: 54%
“…This finding can be considered relevant when referring to data previously outlined in a study aiming to describe the basic immunohistology of burn wound and adjacent unburned skin: An initial peak of Ki67 labeling was reported in both areas just after burn injury, followed by a marked labeling decrease after 20 days post-injury (number of positive cells being ≤5). [12] In the present study with continuous GHB infusion, the evolution pattern was the opposite: The number of positive cells remained quite much high. This could be explained by the mitogen effect of IGF1 on keratinocytes.…”
Section: Discussioncontrasting
confidence: 54%
“…It was not possible to standardise for burn depth, burn treatment, subject age or total burn area. Furthermore, no 'control'uninjured -skin was available for study as it would have been necessary to obtain control tissue from a site removed from the injured area (Langlois et al, 2005). Nonetheless, this study has shown that a temporal pattern to the cellular response to burn injury exists in a non- standardised setting that would be representative of forensic practice.…”
Section: Discussionmentioning
confidence: 97%
“…The material utilised has also been described in previously published studies (Langlois et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…It is presumed the iron in the tissue resulted from an earlier injury at the site that was chosen as the control, which appeared normal with no outward signs of bruising. It has been previously noted that careful consideration has to be given to selection of control sites when studying injuries of the skin [18]. It is unknown how long iron persists in the skin following injury.…”
Section: Discussionmentioning
confidence: 99%